PENGARUH PROPORSI DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015) - Eko Mujiyanto, 13.05.52.0092; Sunarto, Sunarto (Students Journal of Accounting and Banking, 2017)
This study aims to examined and analyzed the effect of proportion of independent commissionerâs board, audit committee, firm size and profitability to firm value on manufacturing companies listed in the Indonesia Stock Exchange.Â The population of this research is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the years 2013-2015 that reported complete annual report and published in Indonesian Capital Market Directory. Samples are included in the criteria of this study were 187 companies using purposive sampling method. This research data analysis methods using the multiple linear regression.Â The results showed that proportion of independent commissionerâs board and Audit Committee has no significant on firm value. Whereas firm size and profitability has positive significant effect on firm value.Keywords:Â Firm Value, Proportion of Independent Commissionerâs Board, Audit Committee, Firm Size and ProfitabilityÂ Â